Etiopathogenesis of Suicide: A Conceptual Analysis of Risk and Prevention Within a Comprehensive, Deterministic Model - Lennon, Jack C. (Frontiers in Psychology, 2019)
Suicide is a rising global health concern receiving disproportionate attention in comparison to other health conditions. In spite of substantial technological and scientific advancements, suicide research has continued to move slowly in terms of clinical translation due to the complexity of neural mechanisms and subjective experiences that seem to underpin this complex human behavior. This paper poses both an argument and a potential solution for these translational issues that are due to large methodological and theoretical gaps between the physical, biological, and psychological sciences. Therefore, the aim is to accomplish five overarching objectives: 1) synthesize current psychiatric and neuroscientific literature on suicide; 2) provide an empirical argument against the mind-brain dichotomy; 3) report epidemiological concerns related to suicide; 4) elucidate the predictability of suicide risk through novel study designs; and, 5) suggest novel mathematical approaches to the prediction of suicide risk using data obtained from these study designs. Thought experiments and philosophical underpinnings are discussed in an attempt to further illuminate potential causes of methodological and epidemiological shortcomings. Ultimately, this paper not only provides substantial support for the predictability of suicide but serves as a focused call for a major paradigm shift in suicide research.